Analysis of the Charge Transfer in CCDS Including the Effect of Surface States and a Varying Fringing Field - Umesh Kumar; P. Bhushan Mital (Active and Passive Electronic Components)
In this paper, a general charge transfer equation is derived that includes the effect of the surface states and does not assume a constant fringing field. Further, a detailed and simple method is presented for the solution of this general charge transfer equation.